Innovation systems for emerging food technologies: evidence from the development of cultured proteins in Thailand - Eichhorst, Waverly; Blaustein-Rejto, Daniel; Shah, Saloni; Smith, Alex; Newton, Peter (Frontiers in Sustainable Food Systems, 2025)
IntroductionUnderstanding how actors and institutions can support the adoption of novel technologies may help identify opportunities for stakeholders to accelerate transitions towards more sustainable production and consumption practices. Little is currently known about how emerging food technologies may be effectively supported in pre-market stages of development, especially in middle- and low-income countries with industrializing economies.MethodsIn this paper, we apply the theoretical framework of technological innovation systems to assess how actors, networks, and institutions are influencing the pre-market development of cultured protein (CP) technologies in Thailand. We used a mixed-methods approach that consisted of 1) a qualitative document review and 2) semi-structured interviews with 17 expert informants.ResultsWe found that various actors have demonstrated preliminary engagement in the development of an innovation system for CP technologies in Thailand. However, technological diffusion will additionally require addressing a need for regulatory approval, manufacturing capacity, scientific and technical expertise, and consumer acceptance.DiscussionStronger evidence of the potential domestic benefits that CP production could bring to Thailand is a prerequisite for stakeholder engagement and mission alignment across sectors. In the near term, transnational coordination may be necessary to help overcome limitations in domestically available expertise. Our findings demonstrate the importance of a convergence in priorities for technological development and reveal a need for further research into how transnational linkages of innovation systems may help address national weaknesses by complementing resources and capabilities at the national level.